Peran Outdoor Learning pada Pembelajaran Menulis Teks Deskripsi Bagi Siswi Kelas VII-C - Asih Riyanti; Andi Nunun May Rizky; Widya Sari; Syila Fadilah; Delly Rusliadi (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to examine the role of the outdoor learning method in teaching descriptive text writing to the female students of Class VII-C at Junior High School Muhammadiyah 2 Tarakan. The background of this research is based on the role of outdoor learning in providing solutions for both educators and students in the teaching and learning process, particularly in learning to write descriptive texts.This study employed a descriptive qualitative approach, using observation as the primary data collection technique, supported by questionnaires, interviews, and documentation as evidence.The findings indicate that learning through the outdoor learning method successfully increased students' learning interest and comprehension of descriptive texts. By directly observing objects outside the classroom, students were able to write descriptions more quickly due to the real-life experiences they gained. Furthermore, conducting lessons outside the classroom created a more enjoyable learning atmosphere and encouraged students to be more active in participating in learning activities.Based on the questionnaire results, all students stated that the use of this method was helpful. Therefore, the outdoor learning method can be considered an effective alternative to improve students’ writing skills.